PEMANFAATAN TALAS, UBI KAYU DAN KEDELAI SEBAGAI BAHAN BAKU PEMBUATAN BERAS ANALOG - Ernilawati Ernilawati; Shanti Fitriani; Rahmayuni Rahmayuni (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This research was to obtain the best formulation of composite flours of taro and cassava in artificial rice making. This research was accomplished in complete randomized design with 5 treatments and 3 repetitions, which was analyzed by ANOVA and followed by Duncan’s at 5%. The treatments of this research were percentages of three material raws (taro flour: cassava flour: soybean flour). They were TU1 (90%:0:10%), TU2 (80%:10%:10%), TU3 (70%:20%:10%), TU4 (60%:30%:10%) and TU5 (50%:40%:10%). The results of analysis showed that the lower taro flour and the higher cassava flour in making of artificial rice would significantly affect water content, water absorbtion, colour, taste, flavour, level of stickiness and overall assessment of hedonic test. The chosen treatment was TU5 which had water content 6,58%, ash content 2,48, protein 8,27%, fat 1,29%, carbohydrate 81,38%, water absorbtion 74,07% and was described as brown-coloured, tasted rather as taro, flavoured as taro and rather sticky and valued by overall assessment as neutral. Keywords: Artificial rice, composite flours, taro and stickiness.